AGRICULTURA: DOS POVOS NÔMADES AOS COMPLEXOS AGROINDUSTRIAIS - Roos, Alana (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2012)
http://dx.doi.org/10.5902/223611705562 Agriculture is a large network of integrated systems that seek to improve their activities, but toreach that level many events occurred and caused agricultural development, making it a complexactivity The main objective of this paper is to ponder the process by which agriculture is set fromthe first agricultural acts to the agroindustrial complex, and understanding the processes that ledto the development of agriculture, as well as analyze phenomena which were necessary for this toactually happen. To explain the evolution of agriculture in Brazil was necessary, first, a literaturesearch, which includes books which range from the emergence of early settlements along therivers of Europe, to the works that mention the formation of the Agroindustrial Complex, afterwriting an article for reasoned. The agriculture, nomadic peoples to Agroindustrial Complex, whichaims to examine in this article, has undergone various modifications, facing different processes fortheir advance, with several relations involving not only, rural areas, but also the political, technical,social and market. To understand evolution of agriculture in Brazil, all these aspects are necessary,because you can not view this fact would not cover such instances, these were indispensable forthe Brazilian agricultural developments. With it shows the complexity of agriculture, as this involves many actions, and such a tangle of relationships, which often is a process that aims tointerests that are not of importance to agriculture, but of interest to persons and / or factors thataim to profit more than production.